2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7319032
|View full text |Cite
|
Sign up to set email alerts
|

Brain Tumour Segmentation based on Extremely Randomized Forest with high-level features

Abstract: Gliomas are among the most common and aggressive brain tumours. Segmentation of these tumours is important for surgery and treatment planning, but also for follow-up evaluations. However, it is a difficult task, given that its size and locations are variable, and the delineation of all tumour tissue is not trivial, even with all the different modalities of the Magnetic Resonance Imaging (MRI). We propose a discriminative and fully automatic method for the segmentation of gliomas, using appearance- and context-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 8 publications
0
44
0
2
Order By: Relevance
“…Previous studies on brain tumor segmentation can be roughly categorized into un-supervised learning based [9][10][11][12] and supervised learning based [13][14][15][16][17][18] methods. A more detailed topical review on various brain tumor segmentation methods can be found elsewhere, e.g., in [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on brain tumor segmentation can be roughly categorized into un-supervised learning based [9][10][11][12] and supervised learning based [13][14][15][16][17][18] methods. A more detailed topical review on various brain tumor segmentation methods can be found elsewhere, e.g., in [6].…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [13] employed superpixel features in a conditional random fields framework to segment brain tumors, but the results varied significantly among different patient cases and especially underperformed in LGG images. A study was proposed in which extremely randomized forest was used for classifying both appearance and context based features and 83% Dice score was achieved [14]. More recently, Soltaninejad et al [16] combined extremely randomized trees classification with superpixel based over-segmentation for a single FLAIR sequence based MRI scan that obtained 88% overall Dice score of the complete tumor segmentation for both LGG and HGG tumor cases.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, random forests (RF) and convolutional neural networks (CNN) have drawn more interest. Some researchers have successfully applied these two groups of algorithms to brain tumor segmentation for MRI images . Random forests represent machine learning algorithms that allow for the tumor classification.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have successfully applied these two groups of algorithms to brain tumor segmentation for MRI images. 4,22,[25][26][27][28][29][30] Random forests represent machine learning algorithms that allow for the tumor classification. Many decision trees are constructed during training, and a class is assigned that claims the most votes of the individual trees during testing.…”
Section: Introductionmentioning
confidence: 99%
“…Helen et al developed a hybrid method for brain tumour segmentation based on clustering, classification and conventional segmentation methods [11]. Several works applied random forests (RF) classification and its variants to segment tumours [12][13][14][15]. In [12] several features including intensity, geometry and asymmetry from multiple modalities are applied to a random forests classifier.…”
Section: Related Workmentioning
confidence: 99%